2016
DOI: 10.1007/s40119-016-0072-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined Right Ventricular Outflow Tract Epicardial and Endocardial Late Potential Ablation for Treatment of Brugada Storm: A Case Report and Review of the Literature

Abstract: A 34-year-old man with Brugada syndrome (BrS) presented with electrical storm, manifested as multiple appropriate shocks from his implantable cardioverter-defibrillator over a period of 7 hours. He had not tolerated prior treatment with quinidine, and had self-discontinued cilostazol citing persistent palpitations. After stabilization with intravenous isoproterenol, an electrophysiology study was performed but no spontaneous or induced ventricular ectopic beats were identified. A three-dimensional (3D) endocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
8
1
Order By: Relevance
“…We did not find, in the literature, any other reports of diastolic potentials identical to ours, except for a clinical case published by Saha et al [21], in 2016. It describes a patient with Brugada syndrome and arrhythmic storm that underwent catheter ablation.…”
Section: Discussioncontrasting
confidence: 65%
“…We did not find, in the literature, any other reports of diastolic potentials identical to ours, except for a clinical case published by Saha et al [21], in 2016. It describes a patient with Brugada syndrome and arrhythmic storm that underwent catheter ablation.…”
Section: Discussioncontrasting
confidence: 65%
“…Many non-invasive and invasive studies have shown that EP abnormalities responsible for cardiac arrhythmias in BrS are located in RVOT and anterior right ventricular area 4, 10, 11, 12, 13, 14. Electrophysiological abnormalities in the form of late potentials, fractionated potentials, split potentials and low voltage areas were noticed in our patients in endocardial as well as epicardial surface of RVOT/right ventricular area as reported by some authors 10, 11, 13, 15. Substrate modification, either endocardial or epicardial has shown to prevent recurrent VT/VF and ICD shocks in these patients 10, 11, 13, 15…”
Section: Discussionsupporting
confidence: 82%
“…Intravenous infusion of isoproterenol may be useful in BrS with ES. There are few reports of successful RF ablation by to prevent recurrence of VT/VF 4, 10, 11, 12, 13, 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed depolarization over the anterior aspect of the RVOT epicardium was suggested as the underlying electrophysiological mechanism in Brugada syndrome, and catheter ablation over this abnormal area resulted in normalization of the Brugada ECG pattern and prevented VF episodes [ 3 ]. A combined epicardial and endocardial ablation strategy for Brugada syndrome targeting low-voltage, fractionated late potentials in the RVOT was reported recently [ 4 ]. We performed endocardial substrate mapping before attempting the epicardial approach; however, there were no abnormal electrocardiograms to target.…”
Section: Discussionmentioning
confidence: 99%